2013
DOI: 10.1556/amicr.60.2013.3.4
|View full text |Cite
|
Sign up to set email alerts
|

Strain differences in the humoral immune response to commensal bacterial antigens in rats

Abstract: We have investigated the immune response to commensal bacterial species in the two inbred rat strains: Dark Agouti (DA) and Albino Oxford (AO). The predominant Gram-negative aerobe in our rats' intestinal bacterial flora was Escherichia coli, while Proteus mirabilis was isolated only from DA rat strain. We report that sera from both DA and AO rat strains contain specific IgG against predominant intestinal flora. Intramuscular administration of commensal bacterial antigens provoked only Th1-type antibody respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…We have shown previously the presence of anti-E. coli IgG antibodies in the sera of non-immunized rats of both DA and AO strains, and this IgG priming was observed against a limited repertoire of E. coli proteins [12]. In order to monitor the immune response to E. coli during inductive phase of arthritis, the On day 14 after immunization with IFA and CFA very weak anti-E. coli IgG binding levels were detected in sera of AO rats ( Fig.…”
Section: Humoral Immune Response To E Coli Following the Immunizatiomentioning
confidence: 89%
See 1 more Smart Citation
“…We have shown previously the presence of anti-E. coli IgG antibodies in the sera of non-immunized rats of both DA and AO strains, and this IgG priming was observed against a limited repertoire of E. coli proteins [12]. In order to monitor the immune response to E. coli during inductive phase of arthritis, the On day 14 after immunization with IFA and CFA very weak anti-E. coli IgG binding levels were detected in sera of AO rats ( Fig.…”
Section: Humoral Immune Response To E Coli Following the Immunizatiomentioning
confidence: 89%
“…We have previously shown that these rat strains show different potential to produce reactive oxygen species [11] and specifi c antibodies [12] in response to commensal bacteria.…”
Section: Introductionmentioning
confidence: 99%
“…More specific to rats, different rat strains exhibited different extent and variability of serum Il6 response 3 hr following Poly I:C MIA ( Murray et al, 2019 ). Furthermore, strain differences have been shown to influence the antibody response to commensal bacterial antigens and the activation state of NK cells in the experimental autoimmune encephalopathy model of multiple sclerosis ( Djuretić et al, 2019 ; Kovačević-Jovanović et al, 2013 ). Therefore, it is possible that the same Poly I:C immune challenge produced different effects in each strain despite our effort to keep other experimental variables the same as our previous study.…”
Section: Discussionmentioning
confidence: 99%